INITIATION OF MEASURES TO END ILLITERACY AMONG ADULTS IN UZBEKISTAN (1924-1928) - Rahmonjon Rasulovich Ahmedov (Journals Park Publishing, 2023)
In this article, after the national-territorial demarcation, the implementation of measures to end illiteracy among the elderly population in the Uzbek SSR and its results are analyzed. Statistical data on the activity of schools for ending illiteracy established in the republic, the number of people involved in these schools, and their national composition in the period before the complete collectivization of agriculture are presented.
Keywords: national-territorial delimitation, Uzbek SSR, ending illiteracy, schools for ending illiteracy, “Attack” movement, women’s schools, literacy level.